Effective acupuncture back pain treatment - Sim, Kwan Yeow. (2009)
This final year report aims to identify the effective acupuncture points for the back pain treatment and develop an intelligent software consultant package. First of all, a brief introduction of the report is introduced. It followed by the literature review in Chapter 2. In the following chapter, literature survey for effective acupuncture for back pain treatment was conducted and a result of 15 common acupuncture points has been identified. In order to provide acupuncture treatment recommendations to TCM practitioners, a system consists of syndromes, diagnosis and acupuncture treatment recommendation is developed. In Chapter 4, based on the information found in previous chapter, the basic design of the intelligent system is discussed. However, due to time constraint, the development of web-based intelligent software consultation package has not been completed yet. An investigation on the body impedance between effective acupuncture points for back pain treatment is carried on in Chapter 5. A conclusion which consists of project summary, knowledge gained by the author and further improvements is made in the last chapter.